PERAN PROGRAM MAGANG DALAM MENDUKUNG KOMPETENSI MAHASISWA KONSENTRASI PEMASARAN DI BIDANG FINANCE AND ACCOUNTING - Resensia Resensia; Deffrinica Deffrinica (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
Internship programs are one of the experiential learning approaches designed to enhance students' competencies through direct involvement in the professional work environment. This study aims to analyze the role of internship programs in supporting the competency development of marketing concentration students assigned to the Finance and Accounting department. This research employed a descriptive qualitative approach, with data collected through observation, interviews, documentation, and literature review. The findings indicate that the internship program significantly contributes to improving students' competencies in terms of knowledge, technical skills, and professional attitudes. Although the participants have an academic background in marketing, they successfully developed competencies in financial administration, preparation of basic financial reports, document management, office application utilization, professional communication, and teamwork. Furthermore, the internship experience broadened students' understanding of the relationship between marketing functions and financial and accounting activities in supporting organizational operations. The internship program not only enhanced students' work readiness but also fostered adaptability, responsibility, discipline, and problem-solving abilities in a professional environment. Therefore, internship programs serve as an effective bridge between theoretical knowledge acquired in higher education and practical experience in the workplace, ultimately producing graduates with competencies that meet the demands of the business and industrial sectors.